Conflicts between healthcare professionals and families of a multi-ethnic patient population during critical care: an ethnographic study. Issue 1 (December 2015) - Van Keer, Rose-Lima; Deschepper, Reginald; Francke, Anneke; Huyghens, Luc; Bilsen, Johan
Abstract Background Conflicts during communication in multi-ethnic healthcare settings is an increasing point of concern as a result of societies' increased ethno-cultural diversity. We can expect that conflicts are even more likely to arise in situations where difficult medical decisions have to be made, such as critical medical situations in hospital. However, in-depth research on this topic is rather scarce. During critical care patients are often unable to communicate. We have therefore investigated factors contributing to conflicts between healthcare professionals and family members from ethnic minority groups in critical medical situations in hospital. Methods Ethnographic fieldwork was done in one intensive care unit of a multi-ethnic urban hospital in Belgium over 6 months (January 2014 to June 2014). Data were collected through negotiated interactive observation, in-depth interviews with healthcare professionals, from patients' medical records, and by making notes in a logbook. Data were analysed by using grounded theory procedures. Results Conflicts were essentially related to differences in participants' views on what constitutes 'good care' based on different care approaches. Healthcare professionals' views on good care were based predominantly on a biomedical care model, whereas families' views on good care were mainly inspired by a holistic lifeworld-oriented approach. Giving good care, from the healthcare professionals' point of view, included great attention to regulations, structured communication, and central decision making. On the other hand, good care from the families' point of view included seeking exhaustive information, and participating in end-of-life decision making. Healthcare professionals' biomedical views on offering good care were strengthened by the features of the critical care context whereas families' holistic views on offering good care were reinforced by the specific characteristics of families' ethno-familial care context, including their different ethno-cultural backgrounds. However, ethno-cultural differences between participants only contributed to conflicts in confrontation with a triggering critical care context. Conclusions Conflicts cannot be exclusively linked to ethno-cultural differences as structural, functional characteristics of critical care substantially contribute to the development of conflicts. Therefore, effective conflict prevention should not only focus on ethno-cultural differentness but should also take the structural organizational characteristics of the critical care context sufficiently into account.